Application of PSAK No.105 on Mudharabah Accounting in Cooperatives BMT Ma'isyatul Ummah Randuagung - Safitri, Nabila; Nastiti , Ari Sita; Aspirandi, Rendy Mirwan (West Science Accounting and Finance, 2025)
Mudharabah financing is a sharia cooperation between shahibul maal (capital owner) and mudharib (business manager), where the Islamic bank provides all the capital, and the customer manages the business. This study aims to analyze the implementation of mudharabah financing and how to apply PSAK 105 to the BMT Ma'isyatul Ummah Cooperative. This study uses a qualitative descriptive research approach. The object of this research is the BMT Ma'isyatul Ummah Randuagung Cooperative which is located on Jl.Raya Randuagung (West Market), Randuagung District, Lumajang Regency, East Java. The application of PSAK 105 to the recognition, measurement, presentation, and disclosure of mudharabah financing at BMT Ma'isyatul Ummah Randuagung is in accordance with PSAK 105. The principle of net profit is used to recognize the income ratio of mudharabah financing business results at BMT Ma'isyatul Ummah Randuagung. In accordance with PSAK 105, mudharabah financing that has matured and has not been paid by the fund manager is recognized as receivables when the receivables are recognized by BMT.